Surviving the COVID-19 Pandemic: Hoteliers’ Resilience - I Gusti Ayu Putu Wita Indrayani (Universitas Pendidikan Ganesha, 2021)
The COVID-19 pandemic has impacted the entire world. The industry experienced a significant downturn. Unprecedented global travel restrictions and government instructions to stay at home are causing the most significant disruption to the global economy. Many hotel employees have been laid off both formally and informally in the current pandemic situation. It results in people losing their income. This study aims to analyze the strategies used by human resources in the tourism sector, especially hospitality, which has been affected by the COVID-19 pandemic to survive in the middle. This study uses an approach using descriptive analysis. Informants who previously worked in the tourism sector and made Covid-19 adapt and implement various strategies simultaneously to survive and be resilient during the pandemic. The methods used to collect data are questionnaires and interviews. The analysis in this study was conducted using a qualitative descriptive method. The research findings reveal the dominance of the strategies adopted by key informants. Entrepreneurial orientation, motivation and effort are the most prominent approaches in an active strategy to solve problems. Former hoteliers gain resilience to survive during the pandemic by empowering skills from past work experience in star hotels and conducting retraining programs through government policies. Human resources in the tourism sector are expected to foster social-based entrepreneurship or opportunities and needs-based entrepreneurship so that businesses remain stable in the future.